Madam Spry and the secret plans - "Cowley, Joy" (Hawthorn; Mimosa McGraw-Hill, 2007)
Violet Spry, the very sly spy and her faithful hound Hugo, has been asked to track down the billionaire Walter J Honeymaker's secret plans
Donated by "Book Planet", Dated 18-4-2025.
Keywords: Detective and mystery fiction